Classification methodology for spare parts management combining maintenance and logistics perspectives. Issue 2 (3rd April 2018) - Teixeira, Catarina; Lopes, Isabel; Figueiredo, Manuel
Abstract : Spare parts management is a function of maintenance management that aims to support maintenance activities, giving real-time information on the available quantities of each spare part and adopting the inventory policies that ensure their availability when required, minimizing costs. The classification of spare parts is crucial to control the vast number of parts that have different characteristics and specificities. Spare parts management involves mainly two areas, maintenance and logistics. Therefore, the integration of both input information is recommended to make decisions. This paper presents a multi-criteria classification methodology combining maintenance and logistics perspectives that intends to differentiate and group spare parts to, subsequently, define the most appropriate stock management policy for each group. The methodology was developed based on a case study carried out in a multi-national manufacturing company and is intended to be included in its computerized maintenance management system to support decision-making.